Selfie: Culture Identity of Surabaya Youth - Idealita Ismanto (Universitas Gadjah Mada, 2020)
The development of the world of technology has its own impact on generation Z and the world of young people today. One of the phenomena is a selfie. The presence of social media has a positive and negative impact on the development of Z generation education. Selfie photos used by teenagers are a forum for sharing expressions and self-identity. To read the signs in generation Z that use selfies as a communication tool, this study aims to explain the contribution of selfie in instagram as popular culture that has an impact on youth identity Surabaya through public space. This study conducted interviews with young men and women in Surabaya High School as a sample. This research was conducted using an exploratory qualitative approach to get a comprehensive and in-depth picture of the identity of youth in Surabaya through selfie. The results showed that The existence of environmental influences that dominate adolescents in making selfie photos to be more acceptable to teenage friendship circles, selfie photos as an arbitrary communication tool for Surabaya youth, in the context of education there is a content of values, namely the need for character education and visual literacy for adolescents as homo digitalis with character in cultural environment.